THE RELATIONSHIP BETWEEN RESPONSIVE FEEDING PRACTICES, MOTHER'S SELF-EFFICACY, FOOD DIVERSITY, AND SOCIOECONOMIC STATUS WITH TODDLER NUTRITIONAL STATUS - Shidiqah, Raysah Sa’diyah; Novianti, Anugrah; Mulyani, Erry Yudhya; Nadiyah, Nadiyah; Utami, Dessy Aryanti; Sundjaya, Tonny (Journal of Indonesian Specialized Nutrition, 2025)
Background: Nutritional issues among toddlers, such as stunting, wasting, and underweight, remain significant health challenges in Indonesia, including in East Jakarta. Several factors influence the nutritional status of toddlers, including responsive feeding practices, maternal self-efficacy, dietary diversity, and socioeconomic factors. This study aims to analyze the relationship between responsive feeding practices, maternal self-efficacy, dietary diversity, and socioeconomic factors with the nutritional status of toddlers in the Duren Sawit Public Health Center, East Jakarta. Methods: This study employed a quantitative approach with a cross-sectional design. Data collection included direct interviews, height/length measurements using a microtoise/infantometer, weight measurements using a digital scale, and a 24-hour dietary recall. Questionnaires were used to assess the independent variables. Data were analyzed using the Chi-Square and Fisher’s Exact Test. Results: The findings indicate that responsive feeding practices, maternal self-efficacy, and dietary diversity significantly influence stunting status (pvalue < 0.05). However, socioeconomic factors (maternal education and household income) did not show a significant relationship on stunting. Furthermore, responsive feeding practices, maternal self-efficacy, dietary diversity, socioeconomic factors (maternal education), and socioeconomic factors (household income) were found to have a significant impact on the wasting status of toddlers. Conclusion: These findings emphasize the importance of interventions based on responsive feeding and enhancing maternal self-efficacy in improving toddler nutritional status. Therefore, educational programs and initiatives focusing on healthy feeding practices and increasing access to nutritious foods are essential to reduce malnutrition rates among toddlers